Canary Wharf : financing and placemaking - Goetzmann, William N. (SAGE Knowledge. Cases., 2017)
Over nearly thirty years, developers of London's Canary Wharf had navigated the project through a variety of economic, financial, and construction crises, at times facing ruin. By 2017, the project was widely recognized as a success - an internationally recognized financial district of 16 million square feet accommodating over 100,000 workers. Yet storm clouds once again threatened the Estate, as the owners had to grapple with the fallout from the U.K.'s decision to leave the European Union (Brexit) and the rise of fintech.